Ageing and employment policies Germany = Vieillissement et politiques de l'emploi : Germany. (Ageing and employment policies., 2005)
In the face of rapid population ageing and the trend towards early retirement, there is a need to promote better employment opportunities for older people. Much has been said about the need for reform of old-age pensions and early retirement schemes but this may not be sufficient to raise employment rates for older people significantly or to reduce the future risk of labor shortages. Both governments and firms will need to take active measures to adapt wage setting to ageing workforces, to address the extent to which other welfare schemes act as pathways to early retirement, to tackle age discrimination and to improve the job skills and working conditions of older workers. In addition, older workers will need to change their own attitudes towards working longer and acquiring new skills. Little is known about what countries have been doing or should be doing in these areas. This report contains a survey of the main barriers to employment for older workers, an assessment of the adequacy and effectiveness of existing measures to overcome these barriers and a set of policy recommendations for further action by the public authorities and social partners.--Publisher summary.